2022
DOI: 10.1177/16878132221093124
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the CNTs nano fluid flow between the two gyrating disks

Abstract: Nanofluids play a prominent role in the development of various electronic structures and technological devices. Herein, we devise new and efficient techniques for overcoming the problems faced by the base fluids. This article describes water-based carbon nanotubes, including two major types of single-wall carbon nanotubes (SWCNT) and multi-wall carbon nanotubes (MWCNT). A mathematical model is considered for unsteady three-dimensional CNTs nanofluids flow with a uniform magnetic field between two revolving dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…A comparative analysis is showcased between SWCNTs and MWCNTs suspended in a base liquid 27,28 . Some researchers 29,30,31 discussed the Single-wall carbon nanotubes (SWCNT) and multiwall carbon nanotubes (MWCNT), the two primary forms of water-based carbon nanotubes. A three-dimensional CNT nanofluid flow model with an unsteady flow and a uniform magnetic field between two rotating discs and also a Darcy-Forchheimer scheme with convective boundary conditions, suction/injection, and thermal radiation are considered 32 .…”
Section: Introductionmentioning
confidence: 99%
“…A comparative analysis is showcased between SWCNTs and MWCNTs suspended in a base liquid 27,28 . Some researchers 29,30,31 discussed the Single-wall carbon nanotubes (SWCNT) and multiwall carbon nanotubes (MWCNT), the two primary forms of water-based carbon nanotubes. A three-dimensional CNT nanofluid flow model with an unsteady flow and a uniform magnetic field between two rotating discs and also a Darcy-Forchheimer scheme with convective boundary conditions, suction/injection, and thermal radiation are considered 32 .…”
Section: Introductionmentioning
confidence: 99%
“…The numerical estimates of the temperature gradient are shown to be diminishing for the convective dissipation effect. Khan et al [2] obtained the analytical solution of the unsteady CNTs nanofluid flow across two gyrating disks. The temperature distribution is assumed to be more accurate the stronger the values of the unsteadiness parameter.…”
Section: Introductionmentioning
confidence: 99%
“…They discovered that the rates of entropy generation decreased when the radiation parameter was increased. Several authors [23][24][25][26][27][28][29] recently provided heat and mass transfer analyses of nanofluid flow among a variety of geometries. Since that time, a significant amount of research that takes MHD into consideration has apparently been carried out, as shown by Al-Kouz et al, 30 Bin Mizan et al, 31 Salawu et al, 32 Shamshuddin et al 33 However, the references that were discussed before only addressed the flat plate surface, there are still voids that may be filled in order to meet the criterion for further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…They discovered that the rates of entropy generation decreased when the radiation parameter was increased. Several authors 2329 recently provided heat and mass transfer analyses of nanofluid flow among a variety of geometries. Since that time, a significant amount of research that takes MHD into consideration has apparently been carried out, as shown by Al-Kouz et al, 30 Bin Mizan et al, 31 Salawu et al, 32 Shamshuddin et al 33…”
Section: Introductionmentioning
confidence: 99%